Pyrethroid as a Substance of Abuse - Pravesh Sharma; Stephen Manning; Regina Baronia; Saira Mushtaq (Case Reports in Psychiatry)
This is a case of a 22-year-old Hispanic male with a history of bipolar disorder and methamphetamine dependence who was admitted after presenting with suicidal ideations by slashing his throat with a machete. The patient had been smoking and inhaling “processed” pyrethroid for about eight weeks as an inexpensive methamphetamine substitute. He reported experiencing a “rush” similar to methamphetamine after using pyrethroid from liquid insecticide that had been heated (electrocuted) or sprayed on hot metal sheets until it crystallized. The patient presented with no significant physical markings or findings but claimed to have his suicidal ideations precipitated by concerns of ill effects of pyrethroid on his health. He also had positive urine drug screen for methamphetamine, which he admitted to using on the day of admission. We conclude that it is important for physicians to maintain a high level of suspicion for alternate and uncommon substances of abuse as well as risks for suicidal tendencies in these patients.